Hepatitis B Virus and B-cell lymphoma: evidence, unmet need, clinical impact, and opportunities - Rosenberg, Maya; Poluch, Maria; Thomas, Colin; Sindaco, Paola; Khoo, Alan; Porcu, Pierluigi (Frontiers in Oncology, 2023)
Nearly a billion people worldwide are infected with the hepatitis B Virus (HBV) and about a third of them have chronic infection. HBV is an important cause of morbidity and mortality, including acute and chronic hepatitis and hepatocellular carcinoma (HCC). Screening and control of primary HBV infection through vaccination represent a major advance in global public health, but large sections of the world population, in both developed and underdeveloped countries, remain unscreened and unvaccinated. In addition to being a global cause of liver disease, an important role of HBV in lymphoma has also emerged. First, the high risk of HBV reactivation in previously infected patients receiving chemo-immunotherapy necessitates the systematic evaluation of HBV serological status in all non-Hodgkin's lymphoma (NHL) cases and preemptive antiviral therapy for those who may have chronic or occult HBV infection. Second, HBV has been shown to infect lymphocytes, namely B-cells, and has been associated with a higher risk of developing B-cell lymphoma, most clearly in countries where HBV is endemic. While the risk of HBV reactivation with chemoimmunotherapy in NHL is well known, the role and the impact of HBV as a global lymphoma risk factor and potential oncogenic driver in B-cells are very poorly understood. Here, we review the clinical and scientific evidence supporting an association between HBV and B-cell lymphoma, with a particular focus on diffuse large B-cell lymphoma (DLBCL) and provide an overview of the estimated impact of HBV infection on the biology and clinical course of DLBCL.We also discuss ways to gain a better insight into the unmet need posed by HBV in lymphoma and whether assessing immune responses to HBV, measuring viral loads, and detecting the presence of HBV-encoded proteins in tumor tissue could be integrated into the molecular and clinical risk stratification of patients with DLBCL.